2011
DOI: 10.4103/0259-1162.84193
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine premedication in relevance to ketamine anesthesia: A prospective study

Abstract: Background:Ketamine-induced hemodynamic pressor response and psychomimetic effects should be attenuated by appropriate premedication. The present study was designed to evaluate the clinical efficacy and safety of dexmedetomidine premedication for balancing the ketamine-induced hemodynamic pressor response and psychomimetic effects.Materials and Methods:A total of 80 normotensive adult consented patients of ASA grade I and II of both genders, aged 21 to 55 years, who met the inclusion criteria for elective surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…Similar effects were observed with study done by Gupta K et al . [ 6 ] who compared the effect of dexmedetomidine with midazolam in ketamine anesthesia. Our study results on hemodynamic parameters were similar to yet another study done by Kolhe et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar effects were observed with study done by Gupta K et al . [ 6 ] who compared the effect of dexmedetomidine with midazolam in ketamine anesthesia. Our study results on hemodynamic parameters were similar to yet another study done by Kolhe et al .…”
Section: Discussionmentioning
confidence: 99%
“…Patients were premedicated with intravenous metoclopramide (10 mg), glycopyrrolate (0.2 mg) followed by intravenous midazolam at a dose of 0.02 mg/kg[ 6 ] which was given slowly over a period of 10 min. After preoxygenation with 100% oxygen, anesthesia was induced with intravenous ketamine (1% solution) at a dose of 1 mg/kg slowly over 30 s.[ 7 ] Anesthetic and surgical techniques were standardized for all the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies in the past have also demonstrated that pretreatment with dexmedetomidine significantly attenuated the cardiovascular and catecholamine responses to tracheal intubation. [7][8][9][10][11][12] However; attenuation was significantly It is a well-known fact that dexmedetomidine reduces the inducing dose of propofol and thiopentone, but in this study we tried to find out that how much beneficial it is when compared to clonidine. 13,14 It was found that the requirement of propofol was reduced after pretreatment with dexmedetomidine as compared to clonidine.…”
Section: Discussionmentioning
confidence: 98%
“…Handa F,Tanaka M, Nishikawa T, Toyooka H [17] conducted a study to determine the effects of oral clonidine premedication on haemodynamic changes during the entire course of ketamine anaesthesia and concluded that oral clonidine 2.5 microgram/kg and 5 microgram/kg attenuate cardiostimulatory effects associated with ketamine induction. Levanen J, Makela ML, Scheinin H [18] studied the effects of dexmedetomidine premedication on ketamine induced cardiostimulatory effects and [19] studied dexmedetomidine premedication in relevance to ketamine anaesthesia. They concluded that the dexmedetomidine premedication effectively attenuated the ketamine induced haemodynamic pressor response and postanaesthetic delirium effects.…”
Section: Introductionmentioning
confidence: 99%